Methodological Aspects of Innovative Activity Management in Network Production Systems - Mansur F. SAFARGALIEV; Gaziz F. MINGALEEV; Albert L. BIKMULLIN; Alexander P. SNEGURENKO (Communications of International Proceedings, 2020)
The article develops methodological aspects of managing innovative activities in networked production systems, including: identifying the challenges of transforming the infocommunication nature of managing modern production systems in the digital economy; the conceptual apparatus of the innovation management system in networked production systems has been expanded; a comparative analysis of project management in non-network and network production systems is carried out, as well as the distinctive features of the categories "production and trading networks" and "network production systems" are shown; revealed the features of material and technical support in traditional and network production systems; the characteristics of the prospects of networkization of the production system of an industrial holding are given on the example of enterprises of the radio-electronic industry.
Keywords: Network; Production System; Digital Economy; Ecosystem; Infrastructure; Freedom; Competition.